Digital financial literacy and self-efficacy in increasing intention to use digital bank with the technology acceptance model theory approach: A literature review - Sumartini, Ade Ruly; Suprapti, Ni Wayan Sri; Piartrini, Putu Saroyini; Sukaatmadja, I Putu Gde (International research journal of management, IT and social sciences, 2024)
This research seeks to look at public acceptance of digital banking, which are the factors that influence the public's intentions in the use of digital banks. Research goes into the field of marketing science with a focus on the study of consumer behavior. The scope of this research is more focused on the process of acquisition to the consumption (use) of digital banks and the intention of using digital banking to carry out banking transactions. This study uses the theory of technology acceptance model approach to respond to the question. This research uses the method of literature review with the range of previous research years used from 2013 to 2022. This research provides a contribution to future research in the development of the model research of the technology acceptance model theory in the digital age.